2012
DOI: 10.1523/jneurosci.6460-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of GluA1 Deletion on the Hippocampal Population Code for Position

Abstract: The GluA1 subunit of AMPA receptors (AMPARs) is critical for hippocampal synaptic transmission and plasticity. Here, we measured the activity of single units from the CA1 region of the hippocampus while GluA1 knock-out (GluA1) and wild-type (WT) mice traversed a linear track. Although overall firing rates were similar, GluA1 Ϫ/Ϫ neurons were more likely to spike in bursts, but at lower burst frequencies, compared with WT neurons. GluA1 Ϫ/Ϫ neurons showed large reductions in all measures of spatial and directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 87 publications
5
50
0
Order By: Relevance
“…Alternatively, the motifs could arise in the medial entorhinal cortex, where neurons show motif-like activity lasting several seconds and robustly driving the CA1, even in anesthetized or sleeping animals 43 . Accordingly, sustained spiking in consecutive theta cycles was reduced, indicative of diminished motifs, in a GluA1 transgenic mouse with diminished distal dendritic inputs, which typically originate in the entorhinal cortex 44 . Motif-field durations could also be modulated by the temporal integration properties of the h current 45 to generate a dorsoventral gradient of field sizes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alternatively, the motifs could arise in the medial entorhinal cortex, where neurons show motif-like activity lasting several seconds and robustly driving the CA1, even in anesthetized or sleeping animals 43 . Accordingly, sustained spiking in consecutive theta cycles was reduced, indicative of diminished motifs, in a GluA1 transgenic mouse with diminished distal dendritic inputs, which typically originate in the entorhinal cortex 44 . Motif-field durations could also be modulated by the temporal integration properties of the h current 45 to generate a dorsoventral gradient of field sizes.…”
Section: Discussionmentioning
confidence: 97%
“…The impaired spatial selectivity in rats in two-dimensional VR is similar to the weak spatial selectivity seen in human studies, in which such pairings are absent as well. Recent studies have shown that a sufficiently large pool of hippocampal neurons can provide accurate spatial information despite impaired spatial selectivity in one-dimensional environments 44 ; such a distributed coding mechanism might also allow rodents and humans to solve spatial tasks in two-dimensional VR. Our results suggest that in human and primate studies in VR, repeated pairing of a rich variety of stimuli, especially between motor and visual cues, could enhance neural activity and spatial selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…20,129,130 . In line with a hypothesis that the hippocampus acquires and encodes spatial information, it was argued that the residual spatial coding in GluA1-lacking neurons may still be sufficient to perform SRM tasks, and that taken across the entire neuronal population the decoding accuracy is still far better than chance levels 128 . It was also argued that SRM tasks might just be less sensitive than SWM tasks, and that working memory performance may be particularly sensitive to place cell disruption because it requires a flexible representation of position that is rapidly modified by trialspecific information.…”
Section: What Is Anxiety?mentioning
confidence: 93%
“…It is clear that, since their inception 1,12 , brain recordings from awake behaving animals have greatly advanced our understanding of how neurons and networks of neurons encode behaviorally relevant events 3,4,13,14 . In particular, brain recordings from genetically modified mice have allowed the identification of molecular cascades that are crucially involved in neural encoding [15][16][17] . Importantly, the technique has only recently been applied to clinically oriented issues 17,18 .…”
Section: Discussionmentioning
confidence: 99%